Stricter U.S. Gas Standards Stalled. - Barlas, S.
Gasoline may be more expensive than ever in the United States, but talk is still cheap on Capitol Hill. This paper discusses the idea of substantially tightening fuel economy standards. Congress tried in previous sessions to increase Corporate Average Fuel Economy (CAFE) standards for passenger automobiles
Keywords: Corporate Average Fuel Economy standards; USA; Gas standards; Gasoline; Passenger automobiles